2020
DOI: 10.1096/fj.201902434r
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes co‐expressing AQP5‐targeting miRNAs and IL‐4 receptor‐binding peptide inhibit the migration of human breast cancer cells

Abstract: Aquaporin‐5 (AQP5) plays a role in breast cancer cell migration. This study aimed to identify AQP5‐targeting miRNAs and examine their effects on breast cancer cell migration through exosome‐mediated delivery. Bioinformatic analyses identified miR‐1226‐3p, miR‐19a‐3p, and miR‐19b‐3p as putative regulators of AQP5 mRNA. Immunoblotting revealed a decrease of AQP5 protein abundance when each of these miRNAs was transfected into human breast cancer MDA‐MB‐231 cells. Quantitative real‐time PCR demonstrated the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 60 publications
2
24
0
1
Order By: Relevance
“…Samples were analyzed as previously described. [48][49][50] The antibodies used are detailed in Supplementary Material.…”
Section: Semiquantitative Immunoblottingmentioning
confidence: 99%
“…Samples were analyzed as previously described. [48][49][50] The antibodies used are detailed in Supplementary Material.…”
Section: Semiquantitative Immunoblottingmentioning
confidence: 99%
“…Thus AQP5 might show promise in anticancer therapy. Indeed, the discovery of three AQP5-regulating miRNAs (miR-1226–3p, miR-19a-3p, and miR-19b-3p) that, by decreasing the translation of AQP5, reduce breast cancer cell migration, supports its further investigation as a possible therapeutic target [ 104 ].…”
Section: Aqp5 and Breast Cancermentioning
confidence: 99%
“…These results suggest that serum miR-19b-3p expression may be an important biomarker for ICC diagnosis, and targeting the miR-19b-3p-CCDC6 axis may be a promising strategy for ICC treatment (26). Park et al (27) has reported that miR-19b-3p can inhibit the migration of breast cancer cells through exosome-mediated delivery by targeting aquaporin-5. Marcuello et al (28) has demonstrated that a plasma 6-miRNA signature (miR-15b-5p, miR-18a-5p, miR-29a-3p, miR-335-5p, miR-19a-3p and miR-19b-3p) can be used to distinguish between colorectal cancer (CRC) or advanced adenoma and healthy individuals.…”
Section: Discussionmentioning
confidence: 89%